2013
DOI: 10.1039/c3cy00125c
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the stereoselective synthesis of 1,3-diols using biocatalysts

Abstract: Nowadays as environmental concerns have became so significant, new reactions and novel catalysts for complicated chemistry are still in high demand despite tremendous advances accomplished through developing cheaper and more versatile chemical catalysts and optimizing the reaction media. As a large number of natural products and synthetic molecules, used as drugs or pharmacological agents, contain a 1,3-diol moiety either in a syn or anti relationship, the development of new protocols utilizing biocatalysts/ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 129 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…As the chiral 3,5-dihydroxyheptanoic acid derivatives represent the key pharmacophore in all of the super-statins [8], major efforts of the academic and industrial communities have been made for their efficient preparation [38][39][40][41][42][43][44][45][46]. In the course of time, biocatalysis [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] evolved as an important platform for greener and more efficient and stereoselective synthesis of 3,5-dihydroxyheptanoic (heptenoic) acid precursors [63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Structure Of Advanced Super-statin Lateral Chain Precursorsmentioning
confidence: 99%
“…As the chiral 3,5-dihydroxyheptanoic acid derivatives represent the key pharmacophore in all of the super-statins [8], major efforts of the academic and industrial communities have been made for their efficient preparation [38][39][40][41][42][43][44][45][46]. In the course of time, biocatalysis [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] evolved as an important platform for greener and more efficient and stereoselective synthesis of 3,5-dihydroxyheptanoic (heptenoic) acid precursors [63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Structure Of Advanced Super-statin Lateral Chain Precursorsmentioning
confidence: 99%
“…In particular, the synthesis of 1,3‐diols is currently of considerable interest in organic chemistry, because of their use as building blocks for drugs or biologically active agents containing 1,3‐diol subunits . Recently, it was reported that the enantioselective organocatalytic aldol addition of acetone to aldehydes can be combined, in a one‐pot procedure, with the diastereoselective enzymatic reduction of the aldol's keto function.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In particular,t he synthesis of 1,3-diols is currently of considerable interesti no rganic chemistry,b ecause of their use as buildingb locks for drugs or biologically active agentsc ontaining 1,3-diol subunits. [6,7] Recently,i tw as reported that the enantioselective organocatalytic aldol addition of acetonet o aldehydes can be combined, in ao ne-pot procedure, with the diastereoselective enzymatic reduction of the aldol's keto function. As ar esult,a ll four stereoisomeric1 ,3-diols can be produced in such aw ay,w ith diastereomeric ratios (dr values) typically > 20:1, and virtually perfect enantiomeric purity (ee > 98 %).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Biocatalysis is an economic and green approach for chiral resolution of a racemic mixture, 3 in which lipase (triacylglycerol ester hydrolases, EC 3.1.1.3) is among the most attractive targets. 1,2 Biocatalysis is an economic and green approach for chiral resolution of a racemic mixture, 3 in which lipase (triacylglycerol ester hydrolases, EC 3.1.1.3) is among the most attractive targets.…”
Section: Introductionmentioning
confidence: 99%